Upaya Pencegahan Resiko Penularan Tuberkulosis di Wilayah Kerja Puskesmas Talise Melalui Program Edukasi : Efforts to Prevent the Risk of Tuberculosis Transmission in the Talise Health Center Working Area Through Education Programs - Nurmalisa, Baiq Emy; Pangaribuan, Helena; Masulilli, Fitria; Collein, Irsanty; Jurana, Jurana; Ismunandar, Ismunandar; Marlin, Marlin (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2024)
Introduction: In 2022, the number of people newly diagnosed with tuberculosis (TB) worldwide will reach 7.5 million. The discovery of TB cases (suspects) in the Talise Community Health Center work area from 2023 to May 2023 was 273 cases. This has increased significantly compared to the discovery of TB cases (suspected) in 2022, which amounted to 343. This community service aims to provide education to prevent the risk of spreading TB in the Talise Health Center working area. This activity method takes place in the waiting room of the Talise Health Center Polyclinic, Palu City, targeting all visitors to the Polyclinic. The activity was held on June 27 2023 with a total of 30 participants. The activities start from the preparation stage, conducting a pre-test, providing education and discussion, and finally conducting a post-test. Results Based on the pretest scores, it shows that the number of participants who have knowledge about TB is in the low category as many as 15 people or 50%, in the sufficient category there are 7 people or 23.3%, and in the high category there are 8 participants or 26.7%. After the discussion and question and answer process, a post test was carried out where the results obtained showed that the number of participants who had knowledge about TB was 2 people or 6.7% in the low category, 12 people or 40% in the sufficient category, and 16 people or 53 in the high category .3%. The conclusion was that there was an increase in participants' knowledge after being given education. Suggestions require sustainable community service activities so that people can apply them in their daily lives.